2005
DOI: 10.1128/jvi.79.15.9842-9853.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide Derived from RNA Recognition Motif 2 of Human La Protein Binds to Hepatitis C Virus Internal Ribosome Entry Site, Prevents Ribosomal Assembly, and Inhibits Internal Initiation of Translation

Abstract: Human La protein is known to interact with hepatitis C virus (HCV) internal ribosome entry site (IRES) and stimulate translation. Previously, we demonstrated that mutations within HCV SL IV lead to reduced binding to La-RNA recognition motif 2 (RRM2) and drastically affect HCV IRES-mediated translation. Also, the binding of La protein to SL IV of HCV IRES was shown to impart conformational alterations within the RNA so as to facilitate the formation of functional initiation complex. Here, we report that a synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…An NS3 protease inhibitor has been developed as a novel antiviral agent, and clinical studies have been performed using this agent; however, the clinical application of this drug will take time because of the occurrence of certain adverse events [8]. The development of an NS5 polymerase inhibitor and an internal ribosome entry site (IRES)-targeting agent is in progress [9][10][11].…”
Section: Hepatitis C Virus (Hcv) Infection Induces Acute Hepatitis Andmentioning
confidence: 99%
“…An NS3 protease inhibitor has been developed as a novel antiviral agent, and clinical studies have been performed using this agent; however, the clinical application of this drug will take time because of the occurrence of certain adverse events [8]. The development of an NS5 polymerase inhibitor and an internal ribosome entry site (IRES)-targeting agent is in progress [9][10][11].…”
Section: Hepatitis C Virus (Hcv) Infection Induces Acute Hepatitis Andmentioning
confidence: 99%
“…32 P]UTP to generate the labeled HCV IRES RNA as described previously (25). The HCV IRES-containing monocistronic construct (HCV luciferase) was linearized with XhoI to prepare HCV Luc RNA, and the HCV bicistronic construct was linearized with PmeI to generate capped bicistronic RNA (Rluc-HCV IRES-Fluc) to use in the in vitro translation studies.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have demonstrated that a 24-mer peptide (LaR2C) derived from the C terminus of RRM (230-300) of La protein competes with the cellular La protein binding to the HCV IRES and interferes with the functional initiation complex formation (25). It appears that LaR2C interferes with 48S ribosome complexes, rendering it incompetent for 60S joining during internal initiation of translation of HCV RNA (25).…”
mentioning
confidence: 99%
“…Since the mechanism of ribosome assembly is unique and fundamentally different from the cap-dependent translation of the host cell mRNA, it can be targeted to selectively inhibit viral protein synthesis and consequently its replication (Dasgupta et al, 2004;Hellen & Sarnow, 2001;Trowbridge & Gowans, 1998). Previously, we have demonstrated the importance of the GCAC sequence near the iAUG for ribosome assembly onto HCV IRES RNA (Pudi et al, 2003(Pudi et al, , 2005. In fact, human La protein (an important host factor) has been shown to bind to the above sites and a peptide derived from the RNA-binding region of La protein has been shown to interfere with the ribosome assembly and inhibit viral RNA translation (Ali et al, 2000;Mondal et al, 2008;Pudi et al, 2004Pudi et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have demonstrated the importance of the GCAC sequence near the iAUG for ribosome assembly onto HCV IRES RNA (Pudi et al, 2003(Pudi et al, , 2005. In fact, human La protein (an important host factor) has been shown to bind to the above sites and a peptide derived from the RNA-binding region of La protein has been shown to interfere with the ribosome assembly and inhibit viral RNA translation (Ali et al, 2000;Mondal et al, 2008;Pudi et al, 2004Pudi et al, , 2005. Here, we have investigated the ability of an shRNA targeting this region of HCV IRES to inhibit translation and replication of viral RNA.…”
Section: Introductionmentioning
confidence: 99%